Late Oligocene–Miocene non-lunulate sand dollars of South America: Revision of abertellid taxa and descriptions of two new families, two new genera, and a new species - Mooi, Rich; Martínez, Sergio A.; Río, Claudia J. Del; Ramos, Maria Inês Feijó (Zootaxa, 2018)
Material for all seven South American species of late Oligocene and Miocene scutelliform, non-lunulate sand dollars (Echinoidea: Clypeasteroida) was examined, resulting in revision of several taxa, and description of a new family, Placatenellidae n. fam., to house Placatenella n. gen. and Camachoaster n. gen. Known only from the state of Pará, Brazil, and previously described as a member of Abertella Durham, 1953, A. complanata Brito, 1981 is redescribed on the basis of analysis of the holotype and subsequently described material from the same region. A. complanata is removed from synonymy with A. pirabensis (Marchesini Santos, 1958), and transferred as the type species of Placatenella n. gen. A new taxon, Camachoaster n. gen., is described to hold C. maquedensis n. sp. The Abertellidae Durham, 1955 is revised and the concept of the genus Abertella restricted to include only those forms with a posterior notch and all interambulacra discontinuous, including A. pirabensis, which is redescribed from the only known specimen, confirming that this species lacks any trace of an anal lunule but possesses features fully congruent with its placement in Abertella. Iheringiellidae n. fam. is established to house the common but taxonomically challenging taxon, Iheringiella Berg, 1898. New data on the occurrence and location of the types of Iheringiella are discussed, and comments on the status of Eoscutella mirandae Parma, 1985 provided. A tabular key to all seven South American non-lunulates is given, along with discussion of the relationship between the posterior notch and the anal lunule.